Break-even Analysis: Basic Model, Variants, Extensions. - Moriarity, Shane R.; Hirsch, Maurice L. (The Accounting Review, 1993)
Reviews the book `Break-Even Analysis: Basic Model, Variants, Extensions,' by Schweitzer et al.